Realized genetic gain in Urochloa hybrids pipeline using ERA trial data - Espitia, Paula; Camelo, Rodrigo; Hernández, Luis Miguel; Aparicio, Johan; Jauregui, Rosa (International Center for Tropical Agriculture, 2023)
The genetic gain of biomass cover and height in the interspecific Urochloa pipeline was estimated by establishing an ERA trial in two locations in Colombia. Each trial included 150 genotypes from seven cycles of selection in different stages, along with genebank accessions and cultivars. The assessed traits were visual biomass, biomass cover calculated from drone images and height. For the genetic gain estimation, we used a two-stage approach considering only the hybrids in the stage 4, selected after multi location trials in Latin America by the Group Papalotla. All the genetic gain rates were positive in the two sites, with higher values for biomass cover in Llanos. Also, the rates were lower when compared to the ones estimated for resistance to spittlebugs (Hemiptera: Cercopidae), suggesting that the main breeding objective for those selection cycles was increasing the antibiosis and tolerance of the hybrids to this pest. The next step is to perform this assessment for nutritional quality parameters.